Mechanisms and management for soil carbon sequestration - Mosier, Samantha, author; Cotrufo, M. Francesca, advisor; Paustian, Keith, advisor; Davies, Christian, committee member; Denef, Karolien, committee member (Colorado State University. Libraries, 2020)
Soil organic matter (SOM) holds more carbon (C) than the atmosphere and terrestrial aboveground biomass combined. SOM also provides many other co-benefits in the form of ecosystem services. The rate at which we lose or sequester more C in soils is of great importance for mitigating the rising atmospheric greenhouse gas concentrations as well as for maintaining the fundamental services that soils provide to humanity. Many of the mechanisms involved in accruing and storing soil C are not entirely clear, and factors like litter chemistry and minerology can all come into play when determining the sequestration potential of a specific ecosystem. Additionally, not all soil C is equal in its turnover time or in its ability to resist disturbance. Therefore it is crucial that we better understand how functionally different soil C pools form and persist in the soil environment. Several "climate smart" soil management practices have been analyzed for their potential to sequester more C. However there are still gaps in our knowledge regarding soil C sequestration and how it can be impacted by land use management. The southeast US is a region with particularly severe soil degradation from poor agricultural management, but also has a high potential for increased soil C sequestration and overall soil health. This dissertation looks at some potential mechanisms and management practices involved with storing more stable soil C in the southeastern US. Mechanisms include how litter chemistry and soil C saturation can enhance or inhibit soil C sequestration. Then, we evaluated management practices from pine plantations and grassland grazing in the southeastern US to evaluate if improved management could increase soil C stocks, their distribution, and overall soil health.